Spectrum availability in the VHF and UHF bands for the deployment of second-generation digital terrestrial television systems in Brazil - Soares, Thiago Aguiar (2022)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2022.